Hydrogen Peroxide Alleviates Nickel-Inhibited Photosynthetic Responses through Increase in Use-Efficiency of Nitrogen and Sulfur, and Glutathione Production in Mustard - Khan, M. I. R.; Khan, Nafees A.; Masood, Asim; Per, Tasir S.; Asgher, Mohd (Frontiers in Plant Science, 2016)
The response of two mustard (Brassica juncea L.) cultivars differing in photosynthetic capacity to different concentrations of hydrogen peroxide (H2O2) or nickel (Ni) was evaluated. Further, the effect of H2O2 on photosynthetic responses of the mustard cultivars grown with or without Ni stress was studied. Application of 50 μM H2O2 increased photosynthesis and growth more prominently in high photosynthetic capacity cultivar (Varuna) than low photosynthetic capacity cultivar (RH30) grown without Ni stress. The H2O2 application also resulted in alleviation of photosynthetic inhibition induced by 200 mg Ni kg-1 soil through increased photosynthetic nitrogen-use efficiency (NUE), sulfur-use efficiency (SUE), and glutathione (GSH) reduced production together with decreased lipid peroxidation and electrolyte leakage in both the cultivars. However, the effect of H2O2 was more pronounced in Varuna than RH30. The greater increase in photosynthetic-NUE and SUE and GSH production with H2O2 in Varuna resulted from higher increase in activity of nitrogen (N) and sulfur (S) assimilation enzymes, nitrate reductase and ATP-sulfurylase, respectively resulting in enhanced N and S assimilation. The increased N and S content contributed to the higher activity of ribulose-1,5-bisphosphate carboxylase under Ni stress. Application of H2O2 also regulated PS II activity and stomatal movement under Ni stress for maintaining higher photosynthetic potential in Varuna. Thus, H2O2 may be considered as a potential signaling molecule for augmenting photosynthetic potential of mustard plants under optimal and Ni stress conditions. It alleviates Ni stress through the regulation of stomatal and non-stomotal limitations, and photosynthetic-NUE and -SUE and GSH production.